Intelligent Communication Through Software Agent Ontology for Multi-site Software Engineering - Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S. (IET, 2004)
Awareness of what work is being done according to the plan, keeping track of which issues have been currently raised and clarified, coordinating meetings to discuss issues, and make unified just-in-time decisions and keep moving forward are big challenges. If everyone working on a certain project is located in the same area, then situational awareness is relatively straightforward; however, the overheads in communications in a multi-site distributed environment can become very large. Consequently, these problems cause developmental delays, as outstanding issues have not been resolved, issues cannot be discussed immediately, or just in time over a multi-site environment. Ontology enables the sharing of an agreement among teams distributed across the sites by making assumptions explicit. The key idea is to have agreement explicitly interpreted by software tools rather than just being implicitly interpreted by human developers. In this paper, we propose development of ontology-based software engineering for multi-site distributed software development utilized software agent.